Development of A Real-Time PCR Assay for Plasmodiophora brassicae and Its Detection in Soil Samples - Jin-ping LI; Yan LI; Yan-xia SHI; Xue-wen XIE; Chai A-li; Bao-ju LI (Journal of Integrative Agriculture)
A SYBR Green I real-time PCR assay was developed to detect and quantify Plasmodiophora brassicae ribosomal DNA (rDNA) and internal transcribed spacer (ITS). A pair of primers PBF1/PBR1 was designed based on the conservative region of rDNA-ITS of P. brassicae. The positive plasmid pB12 was obtained and used as the template to create standard curve. The specificity, sensitivity, and reproducibility of real-time PCR were evaluated respectively. Naturally and artificially infested soil samples containing different concentrations of P. brassicae were detected. The results demonstrated that standard curve established by recombinant plasmid was shown a fine linear relationship between threshold cycle and template concentration. The melting curve was specific with the correlation coefficient of 0.995 and that the amplification efficiency was 93.8%. The detection limit of P. brassicae genomic DNA was approximately 40 copies per 25 μL. The sensitivity of the assay was at least 100-fold higher than conventional PCR. Only DNA from P. brassicae could be amplified and detected using this assay, suggesting the highly specific of this assay. The coefficient of variation was less than 3%, indicating the PCR method revealed high reproducibility. The detection limit in soil samples corresponded to 1 000 resting spores g−1 soil. Bait plants were used to validate the real-time PCR assay. This developed real-time PCR assay allows for fast and sensitive detection of P. brassicae in soil and should be useful in disease management and pest interception so as to prevent further spread of P. brassicae.